„Wiolka mówi o obrzydliwych rzeczach”. O semantyce i funkcji nazw intymnych części ciała w kobiecym stand-upie - Chudzik, Anna (2022)
The topic of this article concerns the names of intimate body parts that appear in the performances of Polish female stand-up comedians. The aim of the considerations is to show the dominant semantic forms of naming intimate parts of the body and to indicate their functions in speech and genre discourse. The article begins with theoretical findings on the genre features of stand-up and the specificity of the vocabulary relating to body parts considered taboo. Further considerations include an analysis of the material divided into the part concerning semantics and the part concerning the function of the studied vocabulary. The methodological approach used in the study is lexical semantics in terms of cognitive linguistics with elements of pragmalinguistics.
Keywords: semantics; language functions; language taboo; stand-up